How to create innovation the ultimate guide to proven strategies and business models to drive innovation and digital transformation - Dieffenbacher, Stefan F.; Hüttinger, Caroline; Zaninelli, Susanne M.; Lines, Douglas; Rein, Andreas (Wiley, 2024)
"In this comprehensive guide to leading innovation Stefan F. Dieffenbacher and his co-authors show you how to become an organization that plays to win. The only book on business innovation you will ever need, it is a truly practical guide to drive innovation and digital transformation in your organization. The book brings together a wealth of experience from 60 distinguished innovation leaders globally. Uniquely, this team has written the very first book on innovation that covers all domains and is end2end. The book is applicable to organizations of all types. Uniquely, this book brings together all of the working methods, separate business innovation models and processes you will ever need; including 50 ready-to-use innovation tools, models, and canvases, which you can download and immediately apply in your organization."--
Untertitel Umschlag und Titelseite abweichend, alternativ: the ultimate guide to prove strategies and #businessmodels for driving #innovation and #digitaltransformation!
Auf dem Umschlag: 50+ proven tools to go from whiteboard to reality
Keywords: Geschäftsmodell; Digitalisierung; Innovationsmanagement; Business enterprises / Technological innovations; Technological innovations / Management